The development of children's thinking its social and communicative foundations - Carpendale, Jeremy I. M. 1957-; Lewis, Charlie; Müller, Ulrich 1964- (Sage, 2018)
"The Development of Children's Thinking offers undergraduate and graduate students in psychology and other disciplines an introduction to several core areas of developmental psychology. It examines recent empirical research within the context of longstanding theoretical debates. In particular, it shows how a grasp of classic theories within developmental psychology is vital for a grasp of new areas of research such as cognitive neuroscience that have impacted on our understanding of how children develop"--Provided by publisher.